The internet and philosophy of science
1 online resource (xi, 246 pages)
Keywords: "This book analyzes the Internet from the perspective of philosophy of science. Conceived in a broad sense, it includes three major layers: (i) the technological infrastructure, (ii) the Web, and (iii) cloud computing, along with apps and mobile Internet. The book focuses on the network of networks from the viewpoint of complexity, both structural and dynamic. In addition to the scientific side, this volume considers the technological facet and the social dimension of the Internet as a novel design. There is a clear contribution of the Internet to science: first, the very development of the network of networks requires the creation of new science; second, the Internet empowers scientific disciplines, such as communication sciences; and third, the Internet has fostered a whole new emergent field of data and information. After the opening chapter, which offers a series of keys to the book, there are nine chapters grouped into four parts: I) Configuration of the Internet and Its Future, II) Structural and Dynamic Complexity in the Design of the Internet, III) Internal and External Contributions of the Internet, and IV) The Internet and the Sciences. The Internet and Philosophy of Science will be of interest to scholars and advanced students working in philosophy of science, philosophy of technology, and science and technology studies"--